To Evaluation of Effectiveness of Chelatory Therapy in Patients with Talassemia - Zaynutdinova D.L; Qudratova M.F; Qo’ziyeva M.G; Muhammadaminova D.R; Axtamov A.J. (Zien Journals, 2022)
The term “thalassemia” refers to a group of autosomal-recessive blood diseases charaeterized by a decrease in the synthesis of one of two types of polypeptide chains of globin (α or β), that form a molecule of adult hemoglobin(HbA, α2β2). This leads to a decrease in the filling of erythrocytes with hemoglobin and anemia. In Uzbekistan, the birth rate with this disease is 10-15 per year. At present in the Republic of Uzbekistan, 184 patients with thalassemia are registered at the Research Institute of Hematology and Blood Transfuzion at the Dispensary.
Keywords: anemia; hemoglobinopathy; thalassemia; hemosiderosis